2023
DOI: 10.1111/cts.13657
|View full text |Cite
|
Sign up to set email alerts
|

Phase I crossover study of DNA‐protein kinase inhibitor peposertib in healthy volunteers: Effect of food and pharmacokinetics of an oral suspension

Andreas Becker,
Axel Krebs‐Brown,
Claudia Vetter
et al.

Abstract: Peposertib is an orally administered inhibitor of DNA‐dependent protein kinase. We evaluated the effect of food on its pharmacokinetics, and examined the pharmacokinetics of an oral suspension (OS) of disintegrated tablets, in a phase I, open‐label, crossover three‐period study (NCT04702698). Twelve healthy volunteers were randomized to one of six treatment sequences. They received a single dose of peposertib 100 mg as film‐coated tablets under fasted or fed conditions (“tablet fasted” or “tablet fed”) or as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although PK findings in Part FE were inconclusive, a subsequent study in healthy volunteers showed only a mild food effect. 43 In biomarker analyses, disease control was not associated with baseline PD-L1 or DNA-PK levels; however, within the few assessable patients in Part B, a potential association between disease control and Ki-67 expression, a proliferation and prognostic marker for multiple cancers, was observed in tumor cells. 44 …”
Section: Discussionmentioning
confidence: 90%
“…Although PK findings in Part FE were inconclusive, a subsequent study in healthy volunteers showed only a mild food effect. 43 In biomarker analyses, disease control was not associated with baseline PD-L1 or DNA-PK levels; however, within the few assessable patients in Part B, a potential association between disease control and Ki-67 expression, a proliferation and prognostic marker for multiple cancers, was observed in tumor cells. 44 …”
Section: Discussionmentioning
confidence: 90%
“…The discovery of the key role of DNA-PK in DNA damage repair highlighted the potential of DNA-PK inhibitors, such as peposertib, to block DNA repair and, therefore, enhance the efficacy of DNA-damaging agents [8]. Peposertib is a potent, selective and orally bioavailable DNA-PK inhibitor, which, in both preclinical models and clinical trials, strongly potentiates the anti-tumor effects of ionizing radiation and DNA DSB-inducing agents, including anthracyclines [8][9][10]. The combination potential of peposertib with various DNA-damaging treatment modalities, including pegylated liposomal doxorubicin (PLD), is currently being evaluated in early-stage clinical studies (e.g., NCT04092270).…”
Section: Introductionmentioning
confidence: 99%